The effects of oral creatine supplementation on performance in single and repeated sprint swimming - Peyrebrune, M. C.; Nevill, M. E.; Donaldson, F. J.; Cosford, D. J. (Journal of Sports Sciences, 1998)
We studied the effects of oral creatine supplementation on sprint swimming performance in 14 elite competitive male swimmers. The subjects performed a single sprint (1 x 50 yards [45.72 m]) and repeated sprint set (8 x 50 yards at intervals of 1 min 30 s) before and after a 5 day period of either creatine (9 g creatine + 4.5 g maltodextrin + 4.5 g glucose day(-1)) or placebo (18 g glucose day(-1); double-blind protocol) supplementation. Venous and capillary blood samples were taken for the determination of plasma ammonia, blood pH and lactate. Mean times recorded for the single 50 yard sprint were unchanged as a result of supplementation (creatine vs control, N.S.). During the repeated sprint test, mean times increased (P< 0.01, main effect time) during all trials, but performance was improved as a result of creatine supplementation (sprints 1-8: control pre-, 23.35+/-0.68 to 26.32+/-1.34 s; control post-, 23.59+/-0.66 to 26.19+/-1.48 s; creatine pre-, 23.20+/-0.67 to 26.85+/-0.42 s; creatine post-, 23.39+/-0.54 to 25.73+/-0.26 s; P < 0.03, group x trial interaction). Thus the percentage decline in performance times was reduced after creatine supplementation (control, 12.7+/-5.7% vs 11.0+/-5.5%; creatine, 15.7+/-4.3% vs 10.0+/-2.5%; P< 0.05, group x trial interaction). The metabolic response was similar before and after supplementation, with no differences in the blood lactate or pH response. Plasma ammonia was lower on the second trial (P< 0.05, main effect trial), but this could not be attributed to the effect of supplementation (group x trial interaction, N.S.). A further urinary analysis study supported these findings by demonstrating an approximately 67% (approximately 26 g) retention of the administered creatine in this group of swimmers after an identical supplementation regimen. In summary, our results suggest that ingesting 9 g creatine per day for 5 days can improve swimming performance in elite competitors during repeated sprints, but appears to have no effect on a single 50 yard sprint. J Sports Sci 1998 Apr;16(3):271-9